Polymorphism in Conservative Structures? The Scapulocoracoids in Skates Genus Psammobatis (Chondrichthyes, Arhynchobatidae) and the Validity of P. parvacauda - Mabragaña, E.; González-Castro, M.; Gabbanelli, V.; Vazquez, D. M.; Díaz de Astarloa, J. M. (Frontiers in Marine Science, 2020)
Skeletal structures, especially the clasper, neurocranium and scapulocoracoids have been widely used to characterize and describe new species of elasmobranchs. Intra and interspecific variation of scapulocoracoids in 3 species of Psammobatis (n=67) from the Southwest Atlantic were analyzed to assess its utility as a diagnostic character in skates. Moreover, based on scapulocoracoids and body morphometric analysis, the validity of Psammobatis parvacauda McEachran, 1983 was evaluated. A remarkable sexual dimorphism in scapulocoracoids was observed in all species in accordance with original descriptions, which was also evident in the Principal Component (PCA) and Discriminant Analyses. The number and arrangement of post-dorsal and post-ventral fenestra was highly variable at intra-specific level, in contrast with original descriptions. Particularly, one of the morphotypes observed in females of P. normani was identical to the one registered in P. parvacauda. Results showed intraspecific variation in this structure, as was previously observed in Sympterygia species. Therefore, this structure should not be used as a diagnostic character in skates, at least for these genera. Regarding body morphometry the PCA showed that P. parvacauda grouped with P. normani females and the cross-validated analysis showed that P. parvacauda was classified in the group of P. normani females. P. parvacauda is only known for its original description (around Malvinas/Falkland Islands) and a likely second specimen, but our analyses revealed lack of diagnostic characteristics. Based on observation and measurement in the holotype of P. parvacauda, and comparisons with congeneric the species is here synonymized with P. normani.